Pendampingan perencanaan Pembangunan Gedung kesenian dan budaya Desa payung kecamatan weleri kabupaten kendal Jawa tengah - Malik Annasir, M. Abdul; Firman, Annas; Tisnawati, Tisnawati; Kumalasari, Dwi; Rabbani, Nauval; Chassy Arsenna, Ariel; Eva Nurdiati, Rani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Arts and culture buildings are one of the infrastructures needed by a village, because apart from being able to preserve culture and art, they can also increase cooperation. Before construction, buildings or public infrastructure must be planned properly according to predetermined specifications, therefore the planning process must be in accordance with the needs or desires of the village. Payung Village, which is one of the villages in Weleri District, Kendal Regency, plans to build an arts and culture building which will function as a place to increase art appreciation, entertainment education, accommodate performing arts which are the cultural products of a culture or society so as to stimulate and awaken creativity. artists and cultural figures in collecting and developing cultural values. In order for the planning to comply with the specifications, it is necessary to provide assistance in making the design and budget plan so that the building to be built will be in accordance with the expectations of the village government and the community. Keywords: Building, Design, RAB